Productivity, nutrient uptake and quality of popcorn and potato in relation to organic nutrient management practices - Meena, B.P.; Kumar, Ashok; Dhar, Shiva; Paul, Sangeeta; Kumar, Arvind (Annals of Agricultural Research, 2016)
Field experiments were conducted to study the quality parameters and nutrient uptake in pop corn- potato cropping sequence as influenced by various levels and sources of nutrients. Results revealedthat the highest N, P and K content in grain and stover, total N, P and K uptake, protein content ingrain, shelling and popping percentage in pop corn were recorded in the treatment receiving RDF,Recommended dose of fertilizers (N120P25K35kg/ha), which were statistically at par with vermicompostand farm yard manure at both levels of nitrogen (equivalent to 120 and 90 kg N/ha). However, leafcompost proved to be the poorest source in terms of total uptake of NPK nutrients. The highest N,P and K content and total nutrient uptake in potato tuber and haulms and specific gravity of tuberswere recorded in the plots with residual fertility of 120 kg N/ha through FYM, which was at par to120 kg N/ha through vermicompost. Application of FYM (equivalent to 90 kg N/ha) to potato ledto significantly higher nutrient content and total N, P and K uptake in tuber and haulms and specificgravity of tubers during both the years.